PL.55 Testing Saliva for the Prediction of Preterm Birth: How Acceptable is This Method to Women at Risk?. (26th April 2013) - Carter, J; Cate, R; Briley, A; Poston, L
Abstract : Background: Despite extensive work to prevent preterm birth (PTB) it is still not possible to accurately predict those women at risk. Previous research 1 has suggested that salivary progesterone may be useful as an indicator of risk. Saliva tests are relatively uninvasive, but the acceptability of this method has not yet been investigated in pregnant women. Aim: The POPPY study aims to investigate salivary progesterone in a large cohort of women (n = >1000) at risk of PTB to support the development a predictive test and to assess acceptability. Method: In addition to providing at least one 5 ml sample of saliva between 20 and 28 weeks' gestation, women at risk of PTB are asked to complete a short acceptability questionnaire (adapted from Sy et al 2). Results: To date, 1042 questionnaires have been completed. Interim results reveal the number of women agreed or strongly agreed that: 1. They liked the test because it was: a) easy/simple to use, n = 816 (78%); b) better than having blood taken, n = 701 (67%); c) convenient, n = 672 (64%); d) quick, n = 600 (58%); 2. They disliked the test because of: a) mouth dryness, n = 300 (29%); b) time taken, n = 234 (22%); c) embarrassment, n = 89 (9%); d) feelings of gagging, n = 73 (7%). 3. 84% of respondents (n = 880) would recommend it to other pregnant women. Conclusion: Although the majority of women found providing saliva for testing acceptable, this was not universal. Consideration must be given to privacy, and the time needed may be reduced if a smaller volume is required. References: Lachelin G, McGarrigle H, Seed P, Briley A, Shennan A, Poston L. Low saliva progesterone concentrations are associated with spontaneous early preterm labour (before 34 weeks of gestation) in women at increased risk of preterm delivery. BJOG 2009; DOI: 10.11 11/j.1471–052832009.02293.x. Sy FS, Rhodes SD, Choi ST, Drociuk D, Laurent AA, Naccash RM, Kettinger LD. The acceptability of oral fluid testing for HIV antibodies. A pilot study in gay bars in a predominantly rural state. Sex Transm Dis 1998;25:211–5.